Efficacy and safety of pegylated interferon plus ribavirin therapy for chronic hepatitis C genotype 6: a meta-analysis. - Xiwei Wang (Public Library of Science (PLoS), 2014)
Background Hepatitis C genotype 6 (HCV-6) is prevalent in Southeast Asia. Data on the efficacy of direct-acting antiviral agents in chronic HCV-6 patients is limited and pegylated interferon (Peg-IFN) plus ribavirin (RBV) combination therapy remains standard therapy for those patients. Aim Meta-analysis was performed to assess the efficacy and safety of Peg-IFN plus RBV combination therapy for chronic HCV-6 patients. Methods Relevant studies were found by database search through Medline, Embase, Web of Science and The Cochrane Library. All published clinical trials assessing the efficacy of Peg-IFN plus RBV combination therapy for chronic HCV-6 patients were included. Sustained virological response rate (SVR) was pooled. We performed additional meta-analyses to compare the SVR outcomes of 24 versus 48 weeks of treatment in four head-to-head trials. Another second meta-analysis was also conducted to compare the efficacy of combination Peg-IFN plus RBV therapy in HCV-6 versus HCV-1 patients. Results Thirteen studies met the inclusion criteria. The pooled SVR of all single arms was 75% (95% CI: 0.68-0.81). The SVR of 24 weeks treatment was significantly lower than that at 48 weeks, with a risk difference of -14% (95% CI: -0.25 to -0.02, p = 0.02). However, when restricted to the patients with rapid virological response (RVR), there was no significant effect on SVR between these two treatment groups, with a risk difference of -1% (95% CI: -0.1 to 0.07, p = 0.67). The SVR in HCV-6 patients was significantly higher than that in HCV-1 patients, with a relative risk of 1.35 (95% CI: 1.16-1.57, p<0.001). Side effects were common, but rarely caused treatment discontinuation. Conclusions The results of this meta-analysis suggest that Peg-IFN plus RBV is effective and safe for HCV-6 patients. Shortening treatment seems to be feasible in HCV-6 patients with RVR when tolerance to treatment is poor. However, this decision should be made cautiously.